Modelo de factibilidad y pertinencia para el proceso de registro calificado en programas de contaduría pública. (2021)
The Ministry of National Education as the governing body of higher education institutions in Colombia, seeks strategies to ensure the quality of education, guaranteeing the continuous improvement of the institution and its respective programs through processes such as the qualified registration, regulated under the current decree 1330 of July 25, 2019. This document seeks to establish a feasibility and relevance study model for the Public Accounting program, developing in a didactic way a proposal that allows institutions to obtain the qualified registration of the program, an instrument of Quality Assurance in 8 Higher Education. The methodology of this research is descriptive with a mixed approach, that is, quantitative because it is based on surveys that are tabulated and results are obtained and qualitative because the information collected is analyzed and interpreted, which allowed establishing the characteristics of the model of the feasibility and relevance study for the process of qualified registration in Public Accounting programs. Finally, the model is a tool applicable every seven years, time established by the norm for this process.